Nevirapine resistance and breast-milk HIV transmission: effects of single and extended-dose nevirapine prophylaxis in subtype C HIV-infected infants. - Anitha Moorthy; Amita Gupta; Ramesh Bhosale; Srikanth Tripathy; Jayagowri Sastry; Smita Kulkarni; Madhuri Thakar; Renu Bharadwaj; Anju Kagal; Arvind V Bhore; Sandesh Patil; Vandana Kulkarni; et al. (PLoS ONE)
Background Daily nevirapine (NVP) prophylaxis to HIV-exposed infants significantly reduces breast-milk HIV transmission. We assessed NVP-resistance in Indian infants enrolled in the "six-week extended-dose nevirapine" (SWEN) trial who received single-dose NVP (SD-NVP) or SWEN for prevention of breast-milk HIV transmission but who also acquired subtype C HIV infection during the first year of life. Methods/findings Standard population sequencing and cloning for viral subpopulations present at > or =5% frequency were used to determine HIV genotypes from 94% of the 79 infected Indian infants studied. Timing of infection was defined based on when an infant's blood sample first tested positive for HIV DNA. SWEN-exposed infants diagnosed with HIV by six weeks of age had a significantly higher prevalence of NVP-resistance than those who received SD-NVP, by both standard population sequencing (92% of 12 vs. 38% of 29; p = 0.002) and low frequency clonal analysis (92% of 12 vs. 59% of 29; p = 0.06). Likelihood of infection with NVP-resistant HIV through breast-milk among infants infected after age six weeks was substantial, but prevalence of NVP-resistance did not differ among SWEN or SD-NVP exposed infants by standard population sequencing (15% of 13 vs. 15% of 20; p = 1.00) and clonal analysis (31% of 13 vs. 40% of 20; p = 0.72). Types of NVP-resistance mutations and patterns of persistence at one year of age were similar between the two groups. NVP-resistance mutations did differ by timing of HIV infection; the Y181C variant was predominant among infants diagnosed in the first six weeks of life, compared to Y188C/H during late breast-milk transmission. Conclusions/significance Use of SWEN to prevent breast-milk HIV transmission carries a high likelihood of resistance if infection occurs in the first six weeks of life. Moreover, there was a continued risk of transmission of NVP-resistant HIV through breastfeeding during the first year of life, but did not differ between SD-NVP and SWEN groups. As with SD-NVP, the value of preventing HIV infection in a large number of infants should be considered alongside the high risk of resistance associated with extended NVP prophylaxis. Trial registration ClinicalTrials.gov NCT00061321.